Residual strength evaluation by DBEM for a cracked lap joint - R. Citarella (Fracture and Structural Integrity)
The present work summarizes a numerical procedure aimed at the evaluation of the residual strength of a cracked lap joint, based on the competing failure mechanisms regulated by the R-curve analysis and plastic collapse. The model adopted for Stress Intensity Factors (SIFs) evaluation is based on the use of the Dual Boundary Element Method (DBEM) within the theoretical frame of Linear Elastic Fracture Mechanics (LEFM). The value of failure load was available from experiments, allowing a comparison with numerical results and consequent validation of the described procedure.